Preoperative risk factors in total thyroidectomy of substernal goiter - Bove A; Di Renzo RM; D'Urbano G; Bellobono M; D'Addetta V; Lapergola A; Bongarzoni G (Dove Medical Press, 2016)
Aldo Bove, Raffaella Maria Di Renzo, Gauro D’Urbano, Manuela Bellobono, Vincenzo D’ Addetta, Alfonso Lapergola, Giuseppe Bongarzoni Department of Medicine, Dentistry and Biotechnology, University “G. d’Annunzio” Chieti-Pescara, Chieti Scalo, Italy Abstract: The definition of substernal goiter (SG) is based on variable criteria leading to a considerable variation in the reported incidence (from 0.2% to 45%). The peri- and postoperative complications are higher in total thyroidectomy (TT) for SG than that for cervical goiter. The aim of this study was to evaluate the preoperative risk factors associated with postoperative complications. From 2002 to 2014, 142 (8.5%; 98 women and 44 men) of the 1690 patients who underwent TT had a SG. We retrospectively evaluated the following parameters: sex, age, histology, pre- and retrovascular position, recurrence, and extension beyond the carina. These parameters were then related to the postoperative complications: seroma/hematoma, transient and permanent hypocalcemia, transient and permanent laryngeal nerve palsy, and the length of surgery. The results were further compared with a control group of 120 patients operated on in the same period with TT for cervical goiter. All but two procedures were terminated via cervicotomy, where partial sternotomies were required. No perioperative mortality was observed. Results of the statistical analysis (Student’s t-test and Fisher’s exact test) indicated an association between recurrence and extension beyond the carina with all postoperative complications. The group that underwent TT of SG showed a statistically significant higher risk for transient hypocalcemia (relative risk =1.767 with 95% confidence interval: 1.131–2.7605, P=0.0124, and need to treat =7.1) and a trend toward significance for transient recurrent laryngeal nerve palsy (relative risk =6.7806 with 95% confidence interval: 0.8577–53.2898, P=0.0696, and need to treat =20.8) compared to the group that underwent TT of cervical goiter. TT is the procedure to perform in SG even if the incidence of complications is higher than for cervical goiters. The major risk factors associated with postoperative complications are recurrence and extension beyond the carina. In the presence of these factors, greater care should be taken. Keywords: substernal goiter, total thyroidectomy, complications